The process of graduation in Occupational Therapy: traces of anxiety (Research, Society and Development, 2021)
Anxiety is something intrinsic to human beings, which can be recurrent in everyday life, which, at lower intensities, is convenient. However, at higher levels, it becomes aggressive, being divided between trait and state anxiety. The anxiety trait (A-trait) refers to relatively stable individual characteristics regarding the way of coping with anxiety-producing situations. The anxiety state (A-state) is defined as an inconstant emotional state that is identified by unpleasant feelings of tension and apprehension, consciously perceived. The study aimed to identify anxiety traits in Occupational Therapy students at a public university. This is a quantitative research, where data collection was performed by means of the Spielberger Anxiety Trait Inventory (Idate-T), being applied through the Internet (online), sent to personal e-mail and also of the class, and data analysis was performed from the simple tabulation software technique and later used Microsoft Excel spreadsheet. The indications of anxiety traits found in the analysis were that the academics who had indication of moderate and high levels of anxiety represented more than ¼ of the public, being 88% women, 9% men and 3% non-binary, hindering the learning process in graduation, bringing biopsychosocial damage. Thus, it is shown the importance of increasing studies on the mental health of Occupational Therapy students and related areas, and that universities think of strategies that can minimize traces of anxiety above normal.